Green functions for stationary problems with nonlocal boundary conditions - Roman, Svetlana; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2008)
In this paper the Green functions for various stationary problems with nonlocal boundary conditions are investigated.We compare Green functions properties for classical boundary conditions with properties of Green functions for problems with nonlocal boundary conditions. Few examples iliustrate such properties.